Divergent Diagnostic Approaches in Investigating Brucellosis: Unveiling Clinical Signs and Infection Rates - R Murugan, Chetan Chaudhary, Monika (Revista Electronica de Veterinaria, 2024)
Brucellosis, a zoonotic infectious disease caused by bacteria of the Brucella species, remains a significant global public health concern, impacting both humans and animals. To arrive at a thorough comprehension of the topic, an extensive evaluation was conducted, which involved examining 60 carefully obtained serum specimens from various demographic groups. These groups comprised veterinary students, those in charge of animal care, para-veterinarians, licensed veterinary technicians and experts in the complex field of synthetic animal conception. The study sought to provide a nuanced view on the number of cases and possible factors of brucellosis among the veterinary healthcare industry in the designated geographic region by deliberately included such a varied array of individuals. The study examined sera sample for brucellosis using various methods, including the “serum agglutination test (SAT), Immunoglobulin G (IgG) and Import General Manifest (IGM) indirect ELISA, Rose Bengal plate test (RBPT) and polymerase chain reaction (PCR)”. Demographic information such as clinical symptoms, age, risk factors and sex was collected through a structured questionnaire. Intermittent fever (71.62%) was the most common clinical sign observed, along with discomfort throughout the body. The guidelines for early identification, therapy and sickness follow-up highlight the need of a high degree of suspicion, perception and a multimodal testing method.